International Monetary Cooperation Since Bretton Woods - James, Harold (International Monetary Fund, 1996)
This comprehensive history, published jointly by the IMF and Oxford University Press, was written to mark the fiftieth anniversary of international monetary cooperation. From the establishment of the postwar international monetary system in 1944 to how the framework functions in a vastly expanded world economy, historian Harol James describes the tensions, negotiations, challenges, and progress of international monetary cooperation. This narrative offers a global perspective on the events and decisions that have shaped the world economy during the past fifty years.